Marker assisted conversion of a high oleic maintainer line into a high oleic CMS line in sunflower (Helianthus annuus L.): Marker assisted conversion of a high oleic maintainer line into a high oleic CMS line in sunflower (Helianthus annuus L.) - AMEENA PREMNATH; N MANIVANNAN; P L VISWANATHAN; S GEETHA (Journal of Oilseeds Research, 2020)
In order to diversify the CMS lines for a sustainable production system of hybrid sunflower seeds with enhanced oleic acid content, the present study was attempted for the first time in India to transfer cytoplasmic male sterility into a newly developed high oleic maintainer line, COSFHO 7B using marker-assisted backcross breeding (MABB) approach. This MABC strategy successfully recovered the recurrent parent genome in BC3F1 generation and decreased heterozygosity of newly developed high oleic CMS plants. Field evaluation of few important agronomic traits of the high oleic CMS line in BC4F1 generation showed that it was comparable to the fertile maintainer counterpart, COSFHO 7B. The present study implies that marker assisted backcross breeding strategy could considerably decrease the time needed for complete recovery of recurrent parent genome.